METHANE EMISSION FROM RUMINANTS AND UTILITY OF PLANT EXTRACTS IN REDUCTION OF METHANOGENESIS - C. Valli; Surej Joseph Bungalavan; M. Ramachandran; V. Balakrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Methane (CH4) is second major gas after carbon dioxide (CO2) responsible for the warming of environment and ozone layer depletion. Although CH4 production is necessary for efficient digestion, it represents an energetic loss of up to 12% of the gross energy intake in ruminants. Methane is produced by strict anaerobes belonging to the sub-group of the Archaea domain. The past decade has shown a lot of interest in the use of plant extracts to mitigate methane production in ruminants. Addition of plant essential oils, can limit the growth of the micro-organisms participating in methane formation in the rumen, thus resulting in the reduction of its production. Reduction of methane production in the rumen ecosystem is possible to achieve with the use of plantsaponins. Tannins have been found to be toxic for many of the rumen microbes, especially ciliate protozoa, fibre degrading microbes and methanogenic bacteria as a result of this methanogenesis in the rumen is reduced.